الشروط المقترنة بعقد الزواج وحكمها شرعا وقانونا: دراسة مقارنة - باوني، محمد Bawni, Mohammed (عبد الفتاح محمود ادريس, 2015)
Coupled with a marriage contract conditions, are often required by the woman or her guardian for her interest, and these conditions, including what scientists agreed on the health of its requirements, some of which have agreed to void, and not to fulfill it, and some of which differed in their health, and its impact on the contract, which accompanied him, and this research review these types of conditions, and judgment on the contract, which Aghernt him, and sentenced fulfilled.
يقترن بعقد النكاح شروط، غالبا ما تشترطها المرأة أو وليها لتحقيق مصلحة لها، وهذه الشروط منها ما اتفق العلماء على صحة اشتراطه، ومنها ما اتفقوا على بطلانه وعدم الوفاء به، ومنها ما اختلفوا في مدى صحته، وأثره على العقد الذي اقترن به، وهذا البحث يستعرض أنواع هذه الشروط، وحكمها على العقد الذي اقرنت به، وحكم الوفاء بها.
Keywords: عقود النكاح -- الشروط -- الأحكام الفقهية -- قانون الأسرة -- الجزائر